2018
DOI: 10.1038/s41598-018-25846-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cannabidiol on impulsivity and memory during abstinence in cigarette dependent smokers

Abstract: Acute nicotine abstinence in cigarette smokers results in deficits in performance on specific cognitive processes, including working memory and impulsivity which are important in relapse. Cannabidiol (CBD), the non-intoxicating cannabinoid found in cannabis, has shown pro-cognitive effects and preliminary evidence has indicated it can reduce the number of cigarettes smoked in dependent smokers. However, the effects of CBD on cognition have never been tested during acute nicotine withdrawal. The present study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 47 publications
2
23
0
1
Order By: Relevance
“…Interestingly, preliminary findings in humans show that cannabidiol reduces cigarette consumption (Morgan et al, 2013), and pleasantness of cigarette cues after overnight abstinence (Hindocha et al, 2018a) in tobacco smokers. In contrast, a recent study has shown that acute administration of a single dose of cannabidiol did not improve memory performance in tasks previously shown to be impaired during cigarette abstinence (Hindocha et al, 2018b). The effects of repeated administration of different doses of cannabidiol on cognition should be evaluated in dependent smokers (Hindocha et al, 2018b), considering the bell-shaped dose response effects widely reported for this compound and higher effectiveness usually revealed after repeated administration (Zuardi et al, 2017).…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, preliminary findings in humans show that cannabidiol reduces cigarette consumption (Morgan et al, 2013), and pleasantness of cigarette cues after overnight abstinence (Hindocha et al, 2018a) in tobacco smokers. In contrast, a recent study has shown that acute administration of a single dose of cannabidiol did not improve memory performance in tasks previously shown to be impaired during cigarette abstinence (Hindocha et al, 2018b). The effects of repeated administration of different doses of cannabidiol on cognition should be evaluated in dependent smokers (Hindocha et al, 2018b), considering the bell-shaped dose response effects widely reported for this compound and higher effectiveness usually revealed after repeated administration (Zuardi et al, 2017).…”
Section: Discussionmentioning
confidence: 94%
“…A detailed schedule of assessments can be found in Supporting information, Table S1. Other assessments are reported elsewhere . All participants provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…In cigarette smokers, acute nicotine abstinence also produced deficits in verbal and spatial working memory and impulsivity (go/no-go, delay discounting, prose recall and N-back tasks). However, conversely to that observed in animal models, such deficits were not reversed by the administration of CBD (800 mg oral) and this compound even increased commission errors on the go/no-go task in comparison to the placebo treatment [115]. Future preclinical and clinical studies should evaluate whether CBD could attenuate the cognitive deficits induced by chronic exposure to cocaine and METH.…”
Section: Possible Mechanisms Involved In the Protective Effects Ofmentioning
confidence: 99%